Bulky Phosphinines: From a Molecular Design to an Application in Homogeneous Catalysis. Issue 27 (13th May 2013) - Weemers, Jarno J. M.; van der Graaff, Willem N. P.; Pidko, Evgeny A.; Lutz, Martin; Müller, Christian
Abstract The design and preparation of an asymmetrically substituted and bulky phosphinine was achieved by introducing sterically demanding substituents into specific positions of a rigid phosphorus‐heterocyclic framework. Compound 5 shows, at the same time, axial chirality and a sufficiently high energy barrier for internal rotation to prevent enantiomerization. Both enantiomers of 5 were isolated by means of chiral analytical HPLC, and their absolute configurations could be assigned by combining experimental data and DFT calculations. Despite its substitution pattern, 5 can still coordinate to transition‐metal centers through the lone pair of electrons on the phosphorus atom. Rapid CH activation on the adjacent aryl substituent at the 2‐position of the phosphorus heterocycle was achieved by using [Cp*IrCl22] (Cp*=1, 2, 3, 4, 5‐pentamethylcyclopentadienyl) as a metal precursor. A racemic mixture of 5 was applied as a π‐accepting low‐coordinate phosphorus ligand in the Rh‐catalyzed hydroformylation of trans‐2‐octene, which showed a clear preference for the formation of 2‐methyloctanal.